Faktor-Faktor Yang Mempengaruhi Minat Beli Baju Di Ramayana Mall Dinoyo Malang - Mawaddah Mawaddah; Nur Hidayati; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThe purpose of this research is to analyze the influence of product quality, price, promosi, lifestyle and location on buying interests UNISMA Students simultaneously in shopping centers Ramayana Mall Dinoyo Malang (MDC).Sampling using purposive sampling technique. The research data was obtained by distributing questionnaires with size sample 105 respondents. The data analysis technique in this study is multiple linear regression analysis using the SPSS statistic 25 application. The results of this study indicate that the product quality, lifestyle, and location variable has a positive and significant effect on buying interest. UNISMA students instead, the price and promotion variable has a positive and significant impact not significant to the buying interest of UNISMA students. Keyword : Product Quality, Price, Promotion, Lifestyle, Location And Buying Interest